Performance of Indonesian Sharia Rural Bank During Covid-19 Pandemic: A Descriptive Analysis - Nurul Fatma Hasan (Department of Islamic Banking, Faculty of Islamic Economics and Business, UIN KH Abdurrahman Wahid Pekalongan, 2022)
This article aims to analyze the performance of Indonesian Sharia Rural Bank during Covid-19 Pandemic. This research took descriptive-quantitative approach of financing composition and financial ratios of Sharia Rural Banks in Indonesia. The data is taken from secondary source, that is Sharia Banking Statistics of 2018-2021. The results show that financing composition by Sharia Rural Banks are still dominated by non-PLS financing. The the financial performance of Indonesian Sharia Rural Bank during the Covid-19 Pandemic was relatively good. Although the number of Sharia Rural Bank has decreased from 167 in 2018 to 163 in November 2021, but all indicators (CAR, ROA, ROE, NPF, and FDR) are still in accordance with Financial Services Authority standards.